2014
DOI: 10.1007/s00259-014-2915-3
|View full text |Cite
|
Sign up to set email alerts
|

[68Ga]PSMA-HBED uptake mimicking lymph node metastasis in coeliac ganglia: an important pitfall in clinical practice

Abstract: Coeliac ganglia show a relevant [(68)Ga]PSMA-HBED uptake in most patients and may mimic lymph node metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
152
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(164 citation statements)
references
References 10 publications
5
152
3
4
Order By: Relevance
“…However, the decision to use 68 Ga-PSMA imaging to rule out metastatic disease before prostatectomy must be made with caution and with an awareness of the patient's disease history and of the potential for false-positive findings. For example, recent studies and case reports have shown high 68 Ga-PSMA uptake in such conditions as schwannomas, celiac ganglia, and even differentiated thyroid cancer (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…However, the decision to use 68 Ga-PSMA imaging to rule out metastatic disease before prostatectomy must be made with caution and with an awareness of the patient's disease history and of the potential for false-positive findings. For example, recent studies and case reports have shown high 68 Ga-PSMA uptake in such conditions as schwannomas, celiac ganglia, and even differentiated thyroid cancer (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…The most useful role of this tracer has been in cases of biochemical recurrence [8]. 68 Ga-PSMA-HBED-CC has been compared to 11 Cfluoromethylcholine in the diagnosis of PC and has been found to be more sensitive in the diagnosis of lymph node, central bone, and liver metastases [9]. Biodistribution studies have revealed uptake of the radiotracer in the lacrimal glands, salivary glands, liver, spleen, kidneys, small and large bowel besides lesions suspicious for PC [10].…”
Section: Discussionmentioning
confidence: 99%
“…Biodistribution studies have revealed uptake of the radiotracer in the lacrimal glands, salivary glands, liver, spleen, kidneys, small and large bowel besides lesions suspicious for PC [10]. Atypical uptake of this tracer has been reported in the celiac ganglion mimicking lymph nodes [11]. Thyroid incidentalomas are sometimes found in patients undergoing FDG PET/CT for unrelated causes and a significant proportion of them have been shown to harbor malignancy [12].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, knowledge of the CT characteristics (e.g., size, shape, and specific location) is crucial for reliable differentiation. In a recent investigation, at least one celiac ganglion with increased PSMA ligand uptake mimicking retroperitoneal lymph node disease was found in 89% of patients undergoing 68 Ga-PSMA-11 PET/ CT examinations (96). Another important limitation is the absence of PSMA overexpression in the primary tumor or its metastases in up to 10% of patients with primary PC or (as mentioned above) decreased PSMA expression in advanced disease (21).…”
Section: Limitations and Pitfalls In Clinical Interpretationmentioning
confidence: 98%